FACTORS INFLUENCING WORK ATTITUDE AMONG ‘Y’ GENERATION (A CASE OF AFRICA NAZARENE UNIVERSITY) - Kamau, John N.; Njau, Mary M.; Wanyagi, Jacinta (European Scientific Journal, ESJ, 2014)
There are three generations active in the work force today that include Baby Boomers (born before 1950), Generation X (born between 1950s and 1980s) and Generation Y (born in the late 1980s to 2000). These generations show different attitudes towards work. The purpose of this study was to determine factors influencing work attitudes among generation Y. The specific objectives of the study were to identify variables that affect generation Y attitude towards work and decompose the identified variables into factors that can be subjected to further analysis. Data was collected using questionnaires from part time students in Africa Nazarene University. Factor analysis was carried out using SPSS version 17 and the study identified eleven factors that express generation Y attitude towards work. These factors include: relationships, ambition, technology friendliness, self-assertiveness, instant orientation, autonomy among others.